The Diffusion of 4.0 Era Innovation in the Implementation of Police Officers’ Job (Surveying the Conduct of Police Officers of Police Regions of the Indonesian National Police) - Ilham Prisgunanto; Alb. Wahyurudhanto; Sutrisno Sutrisno (AIBPM Publisher, 2019)
The diffusion of innovation tells us how, why, and what the new ideas and technology development are in an organization or a group of people. The world is already in 4.0 era characterized by the use of social media, line, email, websites and all network devices in human life. The presence of smart phones makes it easier to access the internet, as well as the work of police officers at work. This research aims at finding out the dominant aspects affecting the application of the diffusion of 4.0 era innovation by police officers in the workplace. Theories employed in the research are theory of organizational communication, theory of the diffusion of era innovation by Everett Rogers, theory of internet networks and theory of culture in organizations. The research method is the positivistic paradigm by processing the quantitative data. The distribution of questionnaires is done by conducting surveys in several Police Regions in Indonesia, such as Jakarta Metropolitan Police Region (Polda Metro Jaya), West Java Police Region (Polda Jawa Barat), Banten Police Region (Polda Banten), Central Java Police Region (Polda Jawa Tengah), South Sulawesi Police Region (Polda Sulawesi Selatan), Southeast Sulawesi Police Region (Polda Sultra), Central Kalimantan Police Region (Polda Kalteng), and South Kalimantan Police Region (Polda Kalsel). There are 30 respondents of each police region; the total number of respondents is 240. The research was conducted for 4 months from September to December 2018. Hypothesis are tested by using correlational between cultural, technological/infrastructure and occupational variables and the application of information technology. The results of the research reveal that the strongest element related to the change in the diffusion of innovation in the work of police officers of the police regions is infrastructure (technology). On the other side, the weakest element is the work culture of the organization. The survey results state that police officers in Indonesia already have an enthusiasm as innovators. But it can become early adopters if the leadership does not provide creative space to develop the potential of the police officers.